Bioactive Compounds from Organic Waste - Parra-Pacheco, Benito; Cruz-Moreno, Byanka A.; Aguirre-Becerra, Humberto; García-Trejo, Juan Fernando; Feregrino-Pérez, Ana Angélica (Molecules (Basel, Switzerland), 2024)
The reuse and reincorporation of waste are the principles of circular economies. Compost, biofuels, animal feed, dyes, and bioactive compounds can be obtained from the revaluation of organic waste. Research on this subject is scarce and limited to specific sectors, such as agriculture and agroindustry, leaving aside others that generate large quantities of organic waste, such as floriculture. The remains of these sectors have a low decomposition rate compared to other organic wastes. They are a source of bioactive compounds (e.g., essential oils, pigments, phenols) that can be reincorporated into the production chain of various industries. This review describes the composition of waste from agroindustry, agriculture, and floriculture, analyzing their potential revalorization as a source of bioactive compounds and an alternative supply source.